Effect of low doses of FSH and season on the in vitro maturation, fertilization and embryo development of bovine oocytes - TAHIR KARAS¸AHIN, (The Indian Journal of Animal Sciences, 2020)
This study was aimed at determining the effect of follicle-stimulating hormone (FSH) and season on the in vitro maturation, fertilization and embryo development of bovine oocytes. Bovine ovaries obtained from a local slaughter house were transported to the laboratory within 2–3 h in a thermos flask containing antibiotic-supplemented physiological saline (0.9%) and at a fixed temperature of 30°C. Bovine oocytes collected in spring and autumn were incubated in culture media containing FSH at concentrations of 0.2 and 0.8 μg/ml. After maturation, oocytes were fertilized. Fertilized oocytes were incubated in CR1aa culture medium for 7 days at 38.5°C for in vitro development. The assessment made after the completion of the maturation process revealed that, for both FSH doses, the maturation rates obtained with the oocytes collected in spring were higher than those obtained with the oocytes collected in autumn. The incubation of the oocytes collected in autumn in culture media supplemented with 0.2 μg/ml of FSH resulted in a low level of oocyte maturation. After maturation, oocytes were subjected to fertilization. Fertilized oocytes were incubated in CR1aa culture medium for 7 days at 38.5°C for in vitro development. In both seasons, 0.8 μg/ml FSH application was higher than the maturation values obtained with 0.2 μg/ml FSH in terms of fertilization and embryo development rates. The study was repeated 9 times for each season. Although there was no significant difference between fertilizations and embryo development in the seasons, better results were obtained in spring season.